The role of veterinary public health in the demand of services for colombian cattle production (2002)
This study applies Stakeholder Analysis to appraise the role of veterinary public health within service demand for cattle production in Colombia after the process of restructuring of veterinary services. An exploratory study of the livestock service sector was carried out over 13 months through individual open-ended interviews at regional and national levels. The study involved five main stakeholders: producers, service providers, government, training institutions and product purchasers. Four regional case studies examined smallholder, dairy, beef and dual purpose cattle production systems. Despite service availability and professional over-supply, low demand for services and unsatisfied needs were detected. Veterinary public health was widely omitted, highlighting the need for the active role that the public sector must have in policy-making for provision of these services. Some policy recommendations which involve all stakeholders are presented. Despite limitations, the potential and value of participative approaches as a complementary tool is emphasized.